Abertura e bloqueio em discursos públicos conflituantes: Portugal, 1961-1974 - Sardica, José Miguel (Lusitania sacra, 2025)
The origins, pre-awareness and pre-dynamics of April 25, 1974 developed within the framework of the multiple transformations that Portugal underwent in the post-World War II period and, above all, in the final phase of the Estado Novo regime, between 1961 and 1974. This text seeks to contribute to the understanding of the path that, in the 1960s and early 1970s, led to the rupture of the April 25. The text is structured in two parts - one contextual, the other analytical. It begins by tracing a synthetic overview of how change began to overcome immobility, from 1961 onwards, and what the Marcelist «spring» and sunset meant between 1968 and the end of the regime. Afterwards, it will look at how that country developed, between 1961 and 1974, different positions and speeches about national life, between the hope of opening, the denunciation of the blockade and the attempt of solutions. For that purpose, ten moments of intervention will be referred to and briefly analyzed, grouped into four sensibilities - official voices of the regime, voices in favor of another regime, voices of the political opposition and voices of the Catholic opposition.